Recent Records of Racket-tailed Treepie Crypsirina temia (Passeriformes: Corvidae) in Kalimantan, Indonesia - Teguh Willy Nugroho; Alexander Kurniawan Sariyanto Putera; Muhammad Iqbal; Happy Ferdiansyah; Ari Noviyono; Abdul Hakim Syah; Fikri El Zafran (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2025)
The existence of the Racket-tailed Treepie Crypsirina temia on the island of Kalimantan, Indonesia, remains unconfirmed, despite several records and two specimens collected in South Kalimantan since the 20th century. During our birdwatching activities in several areas since 2017, we have encountered this bird and documented our sightings on the Burungnesia platform. We also recorded the habitat conditions where the bird was found to assess its habitat suitability in Kalimantan. Between 2017 and the present, we recorded 10 encounters with this bird from four provinces in Kalimantan, Indonesia. Notably, one record is from research conducted on Laut Island, South Kalimantan. The habitat records from the locations where this bird was found provide valuable information on suitable habitats and can serve as a reference for further research on this species in Kalimantan